Predication of coastal erosion by using radar data - Marghany, Maged
A study is conducted to investigate the coastal erosion in short period. Polarized TOPSAR and ERS-1 data are used for this purpose. The statistical model shows that randon transfer model has a good correlation with wave spectral model and vectors of shoreline rate change. The coastal erosion occurred due to the change of wave spectra refraction pattern. The radon transform could be used as a new method to detect a shoreline change from remotely sensed data.